YKL-40 and matrix metalloproteinases as potential biomarkers of inflammation and fibrosis in the development of bronchiolitis obliterans syndrome - Kastelijn, E.A.; van Moorsel, C.H.M.; Ruven, H.J.T.; Korthagen, N.M.; Kwakkel-van Erp, J.M.; van de Graaf, E.A.; Zanen, P.; van Kessel, D.A.; Grutters, J.C (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2013)
Background and objective: The development of bronchiolitis obliterans syndrome (BOS) after lung transplantation is characterized by inflammation, remodeling and fibrosis. Both YKL-40 and matrix metalloproteinase (MMP)-9 have shown to be involved in these processes.We measured serial YKL-40 and MMP-9 serum levels in lung transplant recipients and assessed their usefulness as biomarker for BOS. Furthermore, we investigate the relationship between these two potential biomarkers of BOS and MMP-7. Design: Ten patients with BOS (BOSpos) and 10 matched patients without BOS (BOSneg) were included. Serial serum samples were collected after lung transplantation and prior to BOS. YKL-40, MMP-9 and MMP-7 serum levels were determined by ELISA. Results: The median concentrations of YKL-40 did not differ between BOSpos and BOSneg patients (p > 0.05). The median concentration of MMP-9 in BOSpos patients was significantly higher than in BOSneg patients (p < 0.0001). For MMP-9 as possible risk factor for BOS, a cut off value of 145 ng/ml has a sensitivity of 90% and a negative predictive value of 83%. Longitudinal analysis of YKL-40 andMMP-9 serum levels from the early post-transplant period onwards did not reveal a significant trend in time in both serum levels preceding BOS. In BOSneg patients MMP-9 showed an inverse relationship with MMP-7, that was absent in BOSpos patients. Conclusions: From the moment of transplantation onwards, patients who eventually developed BOS had significantly increased MMP-9 serum levels in comparison with patients who did not develop BOS. Therefore, increased MMP-9 serum levels might be useful as risk factor for BOS.